Hereditary ovarian cancer: biology, response to chemotherapy and prognosis. (September 2009) - Safra, Tamar
Recent evidence has indicated that the prognosis of women with epithelial ovarian cancer who are BRCA -mutation carriers may be better than for noncarriers. Part of the explanation is a higher sensitivity to platinum and other chemotherapies, as was demonstrated in in vitro studies, as well as a possible different biology. BRCA genes are important in double-strand DNA break repair and in other important processes of the cell cycle. Mutation or reduced activity of BRCA genes leads to a higher vulnerability to DNA damage (caused by chemotherapy and radiotherapy) compared with malignant tumors of noncarriers. New targeted drugs, such as poly (ADP-ribose) polymerase-1 and -2 inhibitors, are currently under investigation, as are new biomarkers that will hopefully lead the way to better treatment and longer survival. Testing for the BRCA mutation should be carried out and used as a guide for therapy in most patients with epithelial ovarian cancer.